2023
DOI: 10.1177/21650799221137646
|View full text |Cite
|
Sign up to set email alerts
|

Foot and Ankle Disorders in Nurses Exposed to Prolonged Standing Environments: A Scoping Review

Abstract: Background: Prolonged standing environments constitute an occupational risk factor for nurses, particularly for developing foot and ankle disorders. The definitions and potential relationship to hours spent walking or standing are poorly understood. This scoping review aimed to synthesize the main disorders found on nurses’ ankles and feet, their prevalence, the influence of hours spent walking or standing, and gender differences. Methods: This review followed a previously published protocol. Primary and secon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…The possible explanation might be female nurses were more likely to be affected by ankle-foot pain than male nurses. 41 Female nurses are more likely to sustain ankle-foot pain due to after-work responsibilities including parenting, handling household tasks, insufficient rest time, and lack of exercise. 22 In addition, the present study result is lower than the finding of the study conducted in Iran (59%).…”
Section: Limitations Of the Studymentioning
confidence: 99%
“…The possible explanation might be female nurses were more likely to be affected by ankle-foot pain than male nurses. 41 Female nurses are more likely to sustain ankle-foot pain due to after-work responsibilities including parenting, handling household tasks, insufficient rest time, and lack of exercise. 22 In addition, the present study result is lower than the finding of the study conducted in Iran (59%).…”
Section: Limitations Of the Studymentioning
confidence: 99%
“…Studies showed that the prevalence of foot and ankle pain to be 7.6%. [13] The employment of qualified nurses contributes to both clinical and financial gains in patient care, such as increased patient satisfaction, decreased medication errors, fewer falls, pressure ulcers, and infections linked to healthcare. The ideal nurse-topatient ratio for a given unit is determined by a number of variables, including the severity of the patients' needs, the volume of admissions and discharges, and the amount of experience.…”
Section: Introductionmentioning
confidence: 99%
“… 14 This is related to the characteristics of nurses’ jobs that require walking and standing for a long time, so footwear is not only seen based on physical descriptions but functionally to reduce stress on the foot area. 15 …”
Section: Introductionmentioning
confidence: 99%
“…14 This is related to the characteristics of nurses' jobs that require walking and standing for a long time, so footwear is not only seen based on physical descriptions but functionally to reduce stress on the foot area. 15 Continuous muscle contraction activity causes anaerobic metabolic activity resulting in increased lactic acid. 16 Lactic acid becomes a biomarker of muscle fatigue and increases the risk of WRMDs.…”
Section: Introductionmentioning
confidence: 99%